THE INFLUENCE OF THE BEHAVIORAL APPROACH, BEHAVIORAL CONTRACT TECHNIQUE AND SELF-MANAGEMENT ON CONSUMPTIVE BEHAVIOR - Putri, Regina; Marhani , Marhani; Anuar, Arman Bin; Fahmi, Ainul (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2024)
This study aims to examine the influence of a behavioral approach using behavior contract techniques and self-management on the consumptive behavior of students at Muhammadiyah University Palopo. High consumer behavior among students is often influenced by various factors, including a lack of financial awareness and self-management. In this study, a behavioral approach is used to design interventions in the form of behavior contracts and self-management techniques as methods to reduce uncontrolled consumer behavior. The research method applied is an experiment with a Pre Experimental Design approach. Data were collected through questionnaires measuring the frequency and intensity of consumptive behavior before and after the intervention. The results of the analysis show that the implementation of behavioral contracts and self-management techniques has a significant impact on reducing students consumptive behavior. The decline is indicated by a positive change in students spending patterns. These findings suggest that a behavioral approach, which includes behavior contracts and self-management, is effective in helping students manage their consumer behavior. This can be applied as an intervention strategy in educational settings to promote better financial literacy and self-management.